A biomassa de macrófita como mediadora da relação entre peixes congêneres e invertebrados. - Aleixo, Matheus Henrique Ferreira (2021)
In the study it was verified if the habitat complexity, assessed through macrophyte biomass, can mediate the interaction between fish and invertebrates, and help to explain the coexistence of congeneric species. Fish and invertebrates were sampled in ten macrophytes stand with different biomasses in upper Paraná River floodplain. The abundance and richness of invertebrates, the diet and the niche breadth of Moenkhausia bonita and Moenkhausia forestii were evaluated, as well as the overlap of the diet between the congeneric species. With the increase in macrophyte biomass, there was an increase in the abundance of invertebrates, however, the richness did not show a significant influence from the biomass. The diet of both species differed between macrophytes stands with different biomasses, the main difference being the decrease in invertebrate consumption, mainly aquatic, and the increase in consumption of plants. In addition, the consumption of the items proved to be dependent on their profitability and accessibility in the environment. The niche breadth of both species increased with the increase in macrophyte biomass, but there was no overlap of the niche between them. The results showed that although there was an increase in the invertebrate abundance, there was a decrease in the consumption of this resource, indicating that more complex stands can be more effective refuges for aquatic invertebrates. These results reveal the role of habitat complexity in mediating the interaction between fish and invertebrates, promoting coexistence between them, which helps to explain also the coexistence of ecologically similar fish species.